2010
DOI: 10.2478/s10146-009-0008-x
|View full text |Cite
|
Sign up to set email alerts
|

Methods for determination of labile soil organic matter: An overview

Abstract: Soil organic matter (SOM) can be divided into three main pools: labile, stable and inert. Research over recent years has focused on the labile fraction (LF), as it is considered a quickly reactive indicator of soil productivity and health, and important as a supply of energy for soil micro-organisms. A wide spectrum of analytical methods has been used to determine and/or evaluate LF, based on physical, chemical and biochemical principles. The advantages and disadvantages of each technique are explored in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
68
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(74 citation statements)
references
References 69 publications
2
68
0
4
Order By: Relevance
“…Total SOC is not a useful indicator for monitoring purposes, where the changes in land-use are not drastic. In the last decades, more attention has been paid to the SOC of various lability (Schulz, 2004;Kolář et al, 2009), which has been acknowledged as a good indicator of soil quality and environmental health (Strosser, 2010). Most conventional methods used in total SOC determination have been developed to maximize oxidation and recovery of carbon.…”
Section: Evaluation Of Soil Organic Carbon Stability In Grasslands Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Total SOC is not a useful indicator for monitoring purposes, where the changes in land-use are not drastic. In the last decades, more attention has been paid to the SOC of various lability (Schulz, 2004;Kolář et al, 2009), which has been acknowledged as a good indicator of soil quality and environmental health (Strosser, 2010). Most conventional methods used in total SOC determination have been developed to maximize oxidation and recovery of carbon.…”
Section: Evaluation Of Soil Organic Carbon Stability In Grasslands Ofmentioning
confidence: 99%
“…Thus, in order to identify in which SOC fractions the organic carbon is accumulated, Popov and Tcyplenkov (1994) modified the SOM oxidation method, dividing SOM into 11 pools with different degrees of carbon oxidizability, and called the method "chemo-destructive fractionation". Chan et al (2001) and Strosser (2010) have proposed a similar method by which SOM is divided into four fractions, and called the method "sequential oxidation". The compounds that are part of the labile SOC fraction are biochemically active; they are related to material and energy transformations in the soil, as well as appreciably affect soil fertility (Popov et al, 2004).…”
Section: Evaluation Of Soil Organic Carbon Stability In Grasslands Ofmentioning
confidence: 99%
“…The aging of (OM) has an important influence on the denitrification through soil depth because the disappearance of labile fraction against horizons and time, limits the labile leachate that reaches deeper horizons. [6,7] In addition, microorganisms are strongly influenced by environmental conditions: dissolved oxygen, mineralizable carbon, pH, nutrients (e.g. phosphorus) [8,9], water table elevation [10,11], temperature and other seasonal conditions, [12].…”
Section: Eqmentioning
confidence: 99%
“…Golka (2011) also confirmed that considerable amounts of CO 2 are released from arable soils as a result of excessive mineralisation of soil organic matter. According to Strosser (2010) and , by measuring the level of released CO 2 we may determine the intensity of the mineralisation process.…”
Section: Introductionmentioning
confidence: 99%